Further Insights on Decision-Making Abilities in Compulsive Sexual Behavior Disorder: Findings from the Sex@Brain-Study. - Engel, Jannis; Liebnau, Julia; Müller, Silke M.; Veit, Maria; Kneer, Jonas; Sinke, Christopher; Kruger, Tillmann H. C. (Sexual Health & Compulsivity)
Individuals with Compulsive Sexual Behavior Disorder (CSBD) were hypothesized to have impaired decision-making and tend to choose the short-term rewarding option of a sexually related activity despite long-term negative consequences. We investigated 46 men suffering from CSBD and 38 men without CSBD with two different decision-making paradigms: the Iowa-Gambling-Task as a measurement for decision-making under ambiguity and the Game of Dice Task as an assessment for decision-making under risk. Results indicated no general deficits in decision-making abilities in men with CSBD. Findings are discussed in relation to effects of sexual stimuli and their contribution to categorization of CSBD. The main clinical implication of this study is that, since there are no generalized deficits in decision making in men with CSBD, clinicians need to work with patients to identify more precisely where the decision making deficits are, i.e. an in-depth analysis of situational factors that lead to dysfunctional sexual behavior.